PERSEPSI ORANG DENGAN HIV/AIDS (ODHA) TERHADAP PERLAKUAN KELUARGA HINDU DAN SEKITARNYA - Ni Ketut Sukiani; I Putu Aditya Indra Ardana (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
The number of people living with HIV continues to show an increase every year and stigma and discrimination are still often obtained from their environment. PLWHA experience a double burden, in addition to focus on the development of their disease, PLWHA also experience difficulties in social interaction. This condition tends to make PLWHA depressed so that it will have a negative perspective on the surrounding environment. In the Hindu view it has been taught to avoid deviant behavior and treat humanely, support for healing PLWHA. The study aims to determine the perception of PLWHA towards the treatment of Hindu families, neighbors and Hindu figures. Method: quantitative cross-sectional study by conducting interviews using a questionnaire. Data were analyzed descriptively and Kruskal-Wallis statistical test. Results: Respondent characteristics based on male gender were 52.5% and age range 26-30 years was 36.5%. Respondents who had a high school education level were 25% and respondents who did not work were 22.5%. Perceptions of PLWHA towards the treatment of Hindu families by 40% received normal treatment, and 35% received good treatment. Perception of PLWHA towards neighboring treatment of 37.5% each felt normal treatment and poor treatment. Perception of PLWHA towards the treatment of Hindu figures by 45% received good treatment and by 27.5% received normal treatment. Conclusion: PLWHA still get stigma and discrimination from neighbors around their homes. The majority of PLWHA believe that neighbors have negative perceptions so that they give bad treatment to PLWHA. Early introduction of the concept of Hinduism as a guide in the prevention of HIV / AIDS, strengthening the role of Hindu figures in prevention, performing arts to socialize Hindu concepts, packaged innovatively through appropriate media to increase understanding of the people.